What happened to the knowledge economy? ICT, intangible investment and Britain's productivity record revisited - Mauro Giorgio Marrano; Jonathan Haskel; Gavin Wallis (Queen Mary University of London, Department of Economics, 2007)
A major puzzle is that despite the apparent importance of innovation around the knowledge economy, UK macro performance appears unaffected: investment rates are flat, and productivity has slowed down. We investigate whether measurement issues might account for the puzzle. The standard National Accounts treatment of most spending on knowledge or intangible assets is as intermediate consumption. Thus they do not count as either GDP or investment. We ask how treating such spending as investment affects some key macro variables, namely, market sector gross value added (MGVA), business investment, capital and labour shares, growth in labour and total factor productivity, and capital deepening. We find (a) MGVA was understated by about 6% in 1970 and 13% in 2004 (b) instead of the nominal business investment/MGVA ratio falling since 1970 it is has been rising (c) instead of the labour compensation/MGVA ratio being flat since 1970 it has been falling (d) growth in labour productivity and capital deepening has been understated and growth in total factor productivity overstated (e) total factor productivity growth has not slowed since 1990 but has been accelerating.
Keywords: O47; E22; E01; 330; Intangible assets; Productivity; R&D; Training; Organisational capital; Investment; Wirtschaftswachstum; Produktivit\~AƒÂt; Intangibles Gut; Investition; Informationstechnik; Gro\~AƒÅbritannien; USA